The Possibility of Reform: Micropolitics in Higher Education - Haag, Susan; Smith, Mary Lee (Education Policy Analysis Archives, 2002)
The purpose of this case study was to examine the restructuring of an institution of higher education's teacher preparation program and to assess the possibility for systemic reform.  Although teacher education represents a vital link in not only the educational system but in curricular reform, the increased expectations for educational reform made this institution unavoidably more political.  These conditions meant that the study of micropolitics was critical to understanding how organizations change or fail to initiate change.  Any effort to reform an organization requires examination of the reform effort's underlying assumptions, social and historical context for the reform, and how reform is congruent with the values, ideologies, and goals of the constituents. This case will serve those critiquing reform and also takes the extant K-12 micropolitical research into the heretofore unstudied realm of higher education therefore impacting reform at the post secondary level. Schools are vulnerable to a host of powerful external and internal forces.  They exist in a vortex of government mandates, social and economic pressures, and conflicting ideologies associated with administrators, faculty, and students. Efforts to reform school are confounded by competing political agendas.  At the very least, reform is an opportunity for political action by people in power.  While literature regarding effective schools touts strong leadership and shared values, accomplishing school reform continues to remain problematic. Despite the widespread interest and infusion of resources for restructuring teacher education, the history of educational reform shows that initiatives have often failed.   The study began with the micropolitical hypothesis that the educational system comprises diverse constituencies with differing ideologies regarding schooling.  Qualitative methodology was employed to portray intra-organizational processes, to provide concrete depiction of detail, and to study social change. Micropolitics and symbolic interactionism, the theoretical frameworks for the study, influenced the design and production of research and functioned as the interpretive focus. The study followed a multi method approach to understand meanings in context and to interpret these patterns in light of broader contexts.  We employed the following multiple methods to generate a credible account of constituent ideologies: 23 semi-structured interviews, document review, and observational data.  Data reveal fundamental differences in the images of five constituencies in these areas: curriculum, teachers, pupils, and teacher education and support the micropolitical assertion that systemic reform is unobtainable.